2020
DOI: 10.3390/polym12061310
|View full text |Cite
|
Sign up to set email alerts
|

Probing Interactions in Combined Hydroxide Base Solvents for Improving Dissolution of Cellulose

Abstract: To further understand cellulose-solvent interactions in aqueous hydroxide solutions, cellulose behavior in aqueous solutions of NaOH combined with tetramethylammonium hydroxide (TMAH) or benzyltrimethylammonium hydroxide (Triton B), as well as urea, was investigated. The rheological properties of the solutions were assessed through flow sweeps at different temperatures, and the intermolecular interactions were probed using solvatochromic dyes. The results showed that NaOH combined with TMAH had synergistic eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…after 45 minutes). Taking into account the mentioned observations together with better cellulose solubility in TMAH and Triton B reported in previous works 29,30 better AGE solubility and higher temperature stability of the solutions except for NaOH (Fig. 4), a probable indication could be more occurrence of cascade reaction in NaOH.…”
Section: Papersupporting
confidence: 64%
See 1 more Smart Citation
“…after 45 minutes). Taking into account the mentioned observations together with better cellulose solubility in TMAH and Triton B reported in previous works 29,30 better AGE solubility and higher temperature stability of the solutions except for NaOH (Fig. 4), a probable indication could be more occurrence of cascade reaction in NaOH.…”
Section: Papersupporting
confidence: 64%
“…Recently in our group, cellulose dissolution and the existing stabilizing interactions in aqueous solutions of tetramethylammonium hydroxide (TMAH) and benzyltrimethylammonium hydroxide (Triton B) (Scheme 1) as well as their combination with NaOH have been studied. 29,30 The results show that the addition of TMAH and Triton B to NaOH enhances cellulose solubility and in case of TMAH delays the gelation time, allowing for tuning the solution properties by varying the base composition of the solvent. In this study low concentration of the selected bases has been used to dissolve cellulose and later modify it.…”
Section: Introductionmentioning
confidence: 98%
“…No noticeable aggregates could be detected which further conrms the solution stability at different temperatures while applying low to high shear rates. Previous studies on cellulose solutions in NaOH(aq), tetramethylammonium hydroxide (TMAH), benzyltrimethylammonium hydroxide (Triton B) 67 showed that in NaOH cellulose always shows shear thinning behavior indicative of cellulose aggregates existence within the solution. However, when mixed with either TMAH or The shi of the peak at 65.45 to 62.17 ppm in MorOAc/DMSO and 62.74 ppm in MorOH(aq) is suggesting that the "t-g" conformation of the C6-OH group for the crystalline parts of cellulose I had changed into a "g-t" conformation of cellulose II.…”
Section: Flow Properties Of the Obtained Cellulose Solutions At Diffe...mentioning
confidence: 99%
“…As a result, these negatively charged functional groups would strongly interact with the positively charged MB species (the dominant form of MB at pH > 6) via the proposed electrostatic interactions (Figure c). It should be noted that the deprotonation was likely insignificant under the applied conditions; therefore, only slight improvements in the MB-trapping efficiency were observed based on the pH increase. , …”
Section: Resultsmentioning
confidence: 96%
“…It should be noted that the deprotonation was likely insignificant under the applied conditions; therefore, only slight improvements in the MB-trapping efficiency were observed based on the pH increase. 65,66 Varying the initial methylene blue concentration for the adsorption course in the range of 0−400 ppm was also conducted to determine the maximal adsorption capacity of this BC aerogel (Figure 9). The adsorption capacity for MB considerably increased from 4.1 to 29.7 mg/g with growth in the initial concentration of MB from 10 to 200 ppm, respectively.…”
Section: Materials Characterizationmentioning
confidence: 99%